Changes in and Potential Mechanisms of Circulating IgA+CD27-Class-Switched Memory B Cells in Patients With Allergic Rhinitis - Zheng H; Xu S; Yang R; Jiao WE; Qiao YL; Liu JY; Fan HM; Zhou YT; Ni HF; Chen J; Deng YQ; Chen SM (Journal of Asthma and Allergy)
Han Zheng,1,* Shan Xu,1,* Rui Yang,1,* Wo-Er Jiao,1 Yue-Long Qiao,1,2 Jia-Yu Liu,1 Hui-Ming Fan,1 Yan-Ting Zhou,1 Hai-Feng Ni,3 Jin Chen,1 Yu-Qin Deng,1 Shi-Ming Chen1 1Department of Otolaryngology-Head and Neck Surgery, Renmin Hospital of Wuhan University, Wuhan, Hubei, People’s Republic of China; 2Swiss Institute of Allergy and Asthma Research (SIAF), University of Zurich, Davos, Switzerland; 3Department of Otolaryngology-Head and Neck Surgery, Zhejiang Hospital, Hangzhou, Zhejiang, People’s Republic of China*These authors contributed equally to this workCorrespondence: Yu-Qin Deng; Shi-Ming Chen, Department of Otolaryngology-Head and Neck Surgery, Renmin Hospital of Wuhan University, Wuhan, Hubei, People’s Republic of China, Email bamboo0723@126.com; shimingchen0468@163.comBackground: The role of memory B cells and their subgroups in allergic rhinitis (AR) and allergen immunotherapy (AIT) remains unclear. This study aimed to investigate the characteristics of memory B cells in the circulation of patients with AR and those undergoing AIT, as well as their clinical significance.Methods: This study involved a cohort comprising 32 healthy control subjects, 39 individuals diagnosed with AR, and 31 AR patients who had received AIT for over one year. Visual analog scale (VAS) scores were used for symptom assessment, and the serum concentrations of immunoglobulins and cytokines were quantified. This study evaluated alterations in the proportions of peripheral blood memory B cells and their subpopulations, plasma cells, and various T-cell subsets across the three participant groups.Results: The proportion of IgA+CD27- class-switched memory B cells in the AR group significantly decreased compared to the control group, but significantly increased following AIT (P < 0.05). In AR patients, circulating IgA+CD27- class-switched memory B cells were significantly positively correlated with Treg cells, IL-10, and IL-4 and significantly negatively correlated with IFN-γ, total IgE, sIgE, and VAS scores (P < 0.05). After AIT, the number of circulating IgA+CD27- class-switched memory B cells in AR patients was significantly positively correlated with the number of Treg cells and IL-10 and significantly negatively correlated with the VAS score (P < 0.05).Conclusion: The IgA+CD27- class-switched memory cell subset in human peripheral blood may serve as a potential biomarker for evaluating AR symptoms and treatment efficacy. Its mechanism may be associated with interactions between T and B cells.Keywords: memory B cell, IgA memory B cell, allergic rhinitis